Manufacturing and characterization of an effective and eco‐friendly nano insecticide with the aid of green alga Chlorella vulgaris in contrast to traditional insecticide - Rasha Sattam Hameed; Raghad Jasim Fayyad; Maan Abdul Azeez Shafeeq; Rasha Saad Nuaman (Universitas Gadjah Mada, 2023)
There is a growing demand for the manufacture of eco‐friendly insecticide. This study aimed to establish an aqueous extract of Chlorella vulgaris as a green factory to manufacture nano‐insecticide of titanium nanoparticles to control house flies (Musca domestica) by describing the basic properties of TiO2 solution before and after manufacturing. The absorbance was raised to 0.58, while transmission decreased to 38 under UV‐Visible spectra. Regarding to XRD analysis, seven sharp diffraction peaks appeared for a bulk solution while only three sharp peaks were noticed after phyco‐based synthesis. The crystal size of the prepared titanium nanoparticles was determined to be 27.39 nm. Furthermore, the observed size for bulk particles ranged from 92.33 to 249.6 nm through SEM, while for nanocrystalline the size ranged from 9.395 to 206 nm. Various phytochemicals were detected within the algal extract, including phenols, tannins, alkaloids, flavonoids, resins, and saponins. All of these active compounds participated in nano‐synthesis by acting as reducing and stabilizing agents. Finally, titanium nanoparticles were used as a controlling agent against house flies Musca domestica. In this study, this nanoparticles application also has been compared with traditional insecticide Imidacloprid. The high mortality percentages reached 100% against the first larval stage, 70% against the third larval stage, and 93.3% in adult flies. These mortalities were higher after using Imidacloprid for all tested stages. Many phenotypic distortions were also observed in house flies treated with TiO2 NPs prepared by Chlorella, including failure in pupal emergence and maturity, incomplete development in the head, legs, and wings, and disappearance of the genital organs. The study demonstrated that C. vulgaris is a good candidate for nanomanufacturing and a rich naturally derived nanopesticide.